POLITICAL NEWS SOCIAL MEDIA AND POLITICAL PARTICIPATION 2024 BEGINNER VOTER AT THE UNIVERSITY OF NORTH SUMATRA - Asri Widyanti; Agung Kurniawan Sastro; Efri Ayu A. Br. Surbakti; Einggo Adinata; Anugerah Zebua (Sean Institute, 2023)
This study aims to determine how the relationship between political news on social media and new voters' political participation 2024 at the University of North Sumatra. And what social media is most interested by University of North Sumatra students who are classified as 2024 new voters' in accessing political news. The theories used as support in this research are theories of social media, political communication, and political participation. The method used is descriptive quantitative to describe, examine, and explain something that is studied as it is, and draw conclusions from phenomena that can be observed using numbers. The result of this study is that there is a relationship between access to political news on social media on the political participation of 2024 first-time voters at the University of North Sumatra. The majority of University of North Sumatra students who are classified as 2024 first-time voters are passive participants, which means that students only use their voting rights as a form of participation in general elections. And the most popular social media in accessing political news is Instagram.